Determinants of the Effectiveness of Accounting Information Systems with Asta Brata as Moderating Variables - Ni Putu Ayu Astiti Sari; Gede Adi Yuniarta; I Gusti Ayu Purnamawati (Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine and analyze the effect of transformational leadership, internal control, employee performance, and work experience on the effectiveness of accounting information systems with Asta Brata as the moderating variable at Dharma Kerti Tabanan Hospital. The population in this study was 155 employees, with a sample of 107 employees who use accounting information systems. The analytical method used is SEM using the Smart PLS 3.0 program. The results showed that transformational leadership, internal control, employee performance, and work experience had a positive and significant effect on the effectiveness of the accounting information system. Asta Brata can moderate the effect of transformational leadership and internal control on the effectiveness of accounting information systems, but Asta Brata has not been able to moderate the effect of employee performance and work experience on the effectiveness of accounting information systems at Dharma Kerti Tabanan Hospital.